Peningkatan Literasi Digital Bagi Pelajar SMA Melalui Pelatihan Keamanan Siber Dasar - Atikah Sadariah Nasution; Suerni; Nuraisyah Daulay (STIKES Columbia Asia Medan, 2025)
This community service activity aims to improve the digital literacy of students at SMK Negeri 1 Pancur Batu through basic cybersecurity training. The background of this program stems from the students' low awareness of cyber risks such as phishing, data misuse, and weak digital account management. The method used was a participatory educational approach through training sessions, simulations, and group discussions. The results showed a 42% increase in students’ cybersecurity knowledge based on pre-test and post-test evaluations. Furthermore, behavioral changes were observed, including increased awareness of using strong passwords and the formation of a student cybersecurity group as change agents within the school environment. This activity demonstrates that participatory cybersecurity training can significantly enhance students’ awareness and digital skills.